Preparation, Structure, and Properties of Modified Asphalt with Waste Packaging Polypropylene and Organic Rectorite - Youliang Cheng; QianGang Fu; Changqing Fang; Qingling Zhang; Chan Lu (Advances in Materials Science and Engineering)
The modified asphalt with waste packaging polypropylene (WPP) and WPP/organic rectorite (OREC) was prepared by the melt blending method. The effects of OREC on the physical and aging properties of WPP-modified asphalt were studied. The morphologies, microstructure, and thermal properties of WPP-modified asphalt and WPP/OREC-modified asphalt were characterized by fluorescence microscopy, Fourier transform infrared spectroscopy (FTIR), differential scanning calorimetry (DSC), and thermogravimetry (TG). The results show that the composite-modified asphalt exhibits excellent ductility and plasticity when the contents of WPP and OREC are 4 wt. % and 1.5 wt. %, respectively. The deformation ability, softening point, ductility, and high-temperature storage stability of WPP-modified asphalt can be improved by adding the appropriate content of OREC. It is demonstrated that the composite-modified asphalt has an outstanding operational performance when the content of OREC is in the range of 1.5–2 wt. %. Compared with base asphalt, the high temperature performance of WPP-modified asphalt and WPP/OREC-modified asphalt is also improved significantly.